An analysis of postoperative adverse events following laparoscopic cholecystectomy in a tertiary care hospital - Mukherjee, Ramanuj; Agarwal, Vaibhav; Mohanta, Arup; Mukhopadhyay, Gouri; Samanta, Sudipta (International Surgery Journal, 2019)
Background: Being one of the most commonly performed surgery in the modern era, post-operative complications following laparoscopic cholecystectomy deserve special mention. Though not very life threatening, they are quite common. Considering these aspects, this study aims to identify them and possibly a potential remedy for decreasing the incidence in the future. Methods: This is a retrospective, institution-based, observational and cross-sectional analysis conducted in R.G. KAR Medical College and Hospital over 5 years on 1000 patients undergoing surgery. Here we intend to observe the adverse events following laparoscopic cholecystectomy in the post-operative period. Results: Most of the complications were seen in the age group greater than 40 years(63%) followed by the age group 30-40 years (26%).Adverse events were much more common in females (85%) followed by males (15%). The symptoms appeared mostly during 3-7 days post operatively (57%) followed by 20% within the first 6 hours. Non-specific abdominal pain (28%) was the most common adverse event followed by port-site infection in 16.5% cases. Conclusions: Proper pre-anaesthetic check-up with proper instrument handling with proper caution and before closing confirmation of proper placement of clip and no other unintentional injury anywhere can decrease the post-operative complication.